2012
DOI: 10.1111/j.1748-1716.2012.02408.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age and aerobic fitness: effects on mitochondrial respiration in skeletal muscle

Abstract: Mitochondrial substrate sensitivity is not affected by ageing. When young and middle-aged men are carefully matched for (V)·O2max, mitochondrial respiratory capacity is also similar. However, per mitochondrion respiratory capacity was lower in middle-aged compared to young subjects. Thus, when matched for (V)·O2max, middle-aged seem to require a higher mitochondrial content than young subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 38 publications
7
49
2
Order By: Relevance
“…To maintain skeletal muscle oxidative capacity, mitochondrial density is increased as showed by Van den Broek and co-workers (van den Broek et al, 2010) and in line with the observation made in humans by Dela and co-workers (Larsen et al, 2012).…”
Section: Animal Studiessupporting
confidence: 80%
See 1 more Smart Citation
“…To maintain skeletal muscle oxidative capacity, mitochondrial density is increased as showed by Van den Broek and co-workers (van den Broek et al, 2010) and in line with the observation made in humans by Dela and co-workers (Larsen et al, 2012).…”
Section: Animal Studiessupporting
confidence: 80%
“…had similar skeletal muscle mitochondrial respiratory capacity per wet tissue weight. However, when mitochondrial respiratory capacity was normalized by mitochondrial content, middle-aged subjects showed a lower capacity per mitochondrial unit (assessed by mtDNA content), implying that with age skeletal muscle keeps mitochondrial respiratory capacity increasing mitochondrial density (Larsen et al, 2012).…”
Section: Differences In Between Skeletal Muscles Aerobic Capacity Anmentioning
confidence: 96%
“…57). In agreement, while it has often been reported that mitochondrial content and/or function decline with advancing age (Petersen et al, 2003;Cobley et al, 2012;Trounce et al, 1989;Conley et al, 2000;Short et al, 2005), such differences are generally no longer present when healthy, more active elderly are studied (Rimbert et al, 2004;Dela et al, 1996;Brierley et al, 1996;Cobley et al, 2012;Brierly et al, 1997;Larsen et al, 2012b). It also cannot be excluded that age-related declines in muscle enzyme activities were masked due to a greater proportion/area of type I fibers per mg of muscle tissue analyzed in the older subjects.…”
Section: Discussionmentioning
confidence: 66%
“…As well, mitochondrial dysfunction and reduced oxidative capacity in skeletal muscle have been associated to the pathogenesis of sarcopenia, aging disabilities and frailty (Nair, 2005). Although, there are many studies that report the association between aging and decreased mitochondrial function and content in skeletal muscle, studies comparing young versus older subjects are conflicting in this sense (Hutter et al, 2007;Larsen et al, 2012). For example, in two studies examining mitochondrial content in aged rodent (Mathieu-Costello et al, 2005) and aged human muscle (Callahan et al, 2014) assessed by electron microscopy, considered the gold standard for mitochondrial volume density quantitation (Hepple, 2014), no change with aging was reported whereas Conley and colleagues did observe a decrease in mitochondrial content with human aging when the same muscle (vastus lateralis muscle) was examined using the same method (Conley et al, 2000).…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 98%